PENGARUH TUNJANGAN KINERJA TERHADAP KINERJA PEGAWAI PADA DINAS PERTANIAN KABUPATEN MINAHASA - Jecqueline Fritzie Najoan; Lyndon R. J. Pangemanan; Ellen G. Tangkere (Sam Ratulangi University, 2018)
This study aims to determine the effect of performance allowances on the performance of staff in Minahasa District Agricultural Office. This study was conducted from May to August 2017 from preparation to the writing of research reports. Data used in this research are primary data andsecondary data. Primary data is collected by distributing questionnaires directly to employees for selfcompletion. The population in this study was all employees in Minahasa District Agriculture Office which amounted to 184 employees. Slovin formula is used to determine the number of samples so as to obtain the number of samples of 64 respondents. Data analysis techniques used are validity test, reliability test and simple linear regression analysis, for hypothesis testing using t-test with SPSS version 20 program. The research results showed that the test result t probabilility value of 0.000 < 0.05, which means H0 rejected and H1 accepted. Therefure, the performance allowances significantly influence the performance of employees in the Minahasa District Agricultural Office.*jnkd*